Jenis-jenis Tumbuhan yang Dikonsumsi Oleh Ungko (Hylobates agilis F. Cuvier) di Hutan Pendidikan dan Penelitian Biologi, Universitas Andalas - Esa De Safela; - Syamsuardi; - Rizaldi (Jurnal Biologi Universitas Andalas, 2013)
A study about species of plant consumed by Ungko (Hylobates agilis) at The Biological Education and Research Forest, Andalas University, has been done from July to November 2012. We used ad libitum observation to the gibbon’s feeding behavior and sampled those plants they ate. The samples were processed at Herbarium Andalas University (ANDA), Padang. Seventeen species of plants which belong to eleven families have been recognized as food resources of the gibbons. We described each species of the plants based on morphological characters primerily the part eaten by the gibbon. The results showed that most of the fruit eaten by ungko were fleshy, succulence, and easy to digest. The fruit types were bacca, legume, syconium, capsule and drupe. Keywords: Hylobates agilis, identification, plant species.